Systems of singularly perturbed degenerate integro-differential equations - Zavizion, G. V.; ShkiI, N. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We construct asymptotic solutions of singularly perturbed homogeneous and inhomogeneous systems of integro-differential Fredholm-type equations with a degenerate matrix as the coefficient of the derivative.